Por uma atuação trickster do artista/docente da educação básica: experiências criativas a partir do conto “O Reino Encantado do Duende Simão” - Santos, Rodrigo Azevedo (2020)
The main objective of this study was to develop approaches that privilege experience in teaching Art to preschool children and to provide the teaching artist tools for their teaching practices. This was done through the sharing of a children's tale entitled “Reino Encantado do Duende Simão” to the children from the early childhood school “EMEI Maria Luiza Barbosa de Souza”, located in the city of Uberlândia, Minas Gerais, Brazil. The tale created and presented here was developed for toddlers aged two to five by applying current artistic practices in pedagogy in the classroom environment at the aforementioned school. The direction of this research was guided by the poetic desire, of an academic writing that emerged from the experience of teaching performance in Basic Education. At the same time when implementing the desired academic firmness, it seeks to nourish a playful desire elucidated by other materials - photographs, literary narrative, interviews, reports, etc. Through this experience, I present the framework of an authorial path that certainly, can become a reference for teaching practices, especially in the field of Performing Arts, a space so lacking pedagogical reflections towards Art and its specific practice. Teaching performance was also thought of as a possibility of trickster action (HYDE, 2017). This mode of action is supported by new ways of seeing, conceiving and being in the world, rethinking, especially practices that have already become so rigid in the way of artistic practice in school education. The performance of a trickster teacher deals with the possibility of moving between extraordinary spaces, in subversion to orders, the fundamental role of Art in the school context. Finally, entering this journey required a willingness to transmute into this transgressive figure while consolidating a poetic journey about the multiple possibilities that the exercise of teaching practice grants to the artist in the unusual space of the school.